Key indicators of the labour market 1999 (ILO GenevaCH, 1999)
Highlights the importance of labour market statistics, such as labour force participation, employment, unemployment, educational attainment, hours of work, wages, productivity and labour costs, as well as poverty and income distribution. Assembles labour market data from as many countries as possible. Covers 18 indicators and devotes special attention to specific groups of workers including women and youth.
Keywords: LABOUR MARKET